Discoursing Education Reforms: A Case Study of Post-Handover Education Development in Hong Kong. Issue 6 (2nd November 2018) - Ho, Ching-wai
Abstract: This study adopted a discursive institutional framework to examine how teachers make sense of and understand transformation in their work and workplace during education reforms. Examination of this process is highly significant because it helps us to understand the often misplaced emphasis on workload in analysis of teachers' work pressure in public and academic discussions, which might not reflect the whole picture. In-depth interviews were used to obtain information from the teachers' perspective as front-line practitioners in the education institution. The study identified the discursive processes contributing to the institutionalization of new ideas and practices introduced during education reforms. This article argues that through situating teachers' response to the reform in the relevant sociohistorical context, we can better delineate how meaning negotiation is possible in the moment of institutional change.